Respostas

2014-06-08T19:46:33-03:00
Vc vai fazer isso usando a formula de bhaskara. 

2014-06-08T19:54:56-03:00
2x²+6-12=x
2x²-x-6=0    é uma equação de 2º grau

onde   a=2   b=-1   c=-6

Δ=b²-4.a.c
Δ=(-1)²-4.2.(-6)
Δ=1+48
Δ=49  ⇒ raiz de 49 é 7.



x'=-(-1)+7         1+7        8
   ¨¨¨¨¨¨¨¨¨¨¨=  ¨¨¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨= 2
      2.2              4          4


x=-(-1)-7         +1-7         -6                                  3
   ¨¨¨¨¨¨¨¨¨¨¨¨=   ¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨¨¨¨=simplificando    - ¨¨¨¨¨¨
       2.2              4          4  ¨                               2



S:(2, -3 / 2)